Gender Performativity and Resistance: A Reading of Power Structures in Joanne Harris’ Chocolat Series - S. Rajeswari; Dr S. Anitha (ILN Journal: Indian Literary Narratives, 2025)
This article investigates how Joanne Harris’s Chocolat series: Chocolat (1999), The Lollipop Shoes (2007), Peaches for Monsieur le Curé (2012), and The Strawberry Thief (2019), redefines female identity and resistance through the intersection of food, gender, and power. Drawing on Judith Butler’s notion of Gender Performativity and Michel Foucault’s discourse on power and resistance, the study adopts a qualitative method of close textual analysis. The analysis foregrounds how culinary practices in Harris’s novels function as sites of subversion against patriarchal and religious authority, with food emerging not only as a medium of pleasure but also as an instrument of agency. Characters such as Vianne, Josephine, Rosette, Morgane, and Zozie embody different dimensions of resistance, disrupting societal norms of gendered roles and reshaping the dynamics of community and identity. The article suggest that Harris portrays women as active agents who resist societal oppression through everyday practices, especially cooking, caregiving, and self-expression. The novels emphasize culinary resistance as a feminist strategy, highlighting how women reclaim power and autonomy within restrictive cultural and religious frameworks. Harris demonstrates that gender roles are socially constructed and can be resisted through performative acts that transform ordinary practices into tools of empowerment. This study concludes that Harris’s narratives critique rigid structures of power and propose an alternative vision of female agency grounded in food, creativity, and communal care. Future research may extend this inquiry by exploring culinary resistance in global women’s writing, situating Harris within broader literary food studies.